1993
DOI: 10.1159/000310409
|View full text |Cite
|
Sign up to set email alerts
|

Topical Immunoglobulins for Epithelial Herpes Simplex Keratitis

Abstract: A new immunoglobulin preparation for topical administration in the eye has been developed. The tolerance to this preparation was tested in a phase I/II study, in combination with the antiviral drug trifluorothymidine, in 5 patients with untreated episodes of herpes simplex epithelial keratitis. The clinical course of these patients was within usual limits, with a mean healing time of 6.6 days (range 2-15 days). No undesirable effects were observed. Our findings suggest that this new treatment modality is safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Interestingly, it has recently been described that in pa tients affected by herpetic keratitis, the topical administra tion of anti-HSV human immunoglobulins seems to in crease the efficacy o f antiviral therapy in the recovery from epithelial keratitis [27]. In spite of the partial results ob tained in this open trial, which are most likely related to the kind of Ig preparation used for local administration, this treatment modality may deserve further attention.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, it has recently been described that in pa tients affected by herpetic keratitis, the topical administra tion of anti-HSV human immunoglobulins seems to in crease the efficacy o f antiviral therapy in the recovery from epithelial keratitis [27]. In spite of the partial results ob tained in this open trial, which are most likely related to the kind of Ig preparation used for local administration, this treatment modality may deserve further attention.…”
Section: Discussionmentioning
confidence: 80%
“…Studies have shown that in severe infections, they act synergistically with antibiotics with immunomodulatory and additional anti-inflammatory activity, too [ 40 , 41 ]. While the role of IVIG in severe suppurative keratitis in humans is unclear, a study on a mouse ocular infection model demonstrated that treating epithelial herpes simplex keratitis with topical immunoglobulins attenuates the spread and incidence rate of HSV-1 [ 42 ]. In a recent study, IVIG was used as rescue treatment in a ganciclovir-resistant cytomegalovirus retinitis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this treatment are the corneal toxicity associated with its use and the inability to treat resistant strains of the Herpes simplex virus. Consequently, work is currently underway to develop a virus-neutralizing topical antibody therapy (Berdugo et al, 2012;Klager et al, 1993). Bacterial infections of the eye normally respond well to an appropriate antibiotic treatment.…”
Section: Ocular Usementioning
confidence: 99%